PENGUJIAN KUALITAS AIR LIMBAH INDUSTRI TAHU DI DESA KUNCEN KECAMATAN PADANGAN - Oktavianus Cahya Anggara Cahya Anggara; Ahmad Abdul Ali Asyrofi; Dewi Rosyita Sya Roni; Angger Bayu Purnomo Putro (Politeknik Negeri Sriwijaya, 2023)
Tofu liquid waste is a by-product of the tofu industry when processing soybeans into tofu. Based on the Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014, tofu liquid waste has a maximum parameter content of BOD 150 mg/L, COD 300 mg/L, TSS 200 mg/L and pH between 6-9. Tofu liquid waste also contains organic matter, 0.1% carbohydrates, 0.42% protein, 0.13% fat, 4.55%, 1.74% phosphorus and 98.8% water. This study aims to identify the quality parameters of tofu industrial wastewater in Kuncen Village, Padangan District, Bojonegoro Regency. Based on the Regulation of the Minister of Environment Number 5 of 2014 concerning Soybean Management Waste Quality Standards, the results of testing the Characteristics of tofu liquid waste, the Temperature parameter of 55 ºC does not meet the quality standard of 30 ºC. The test results for the pH parameter of 5 do not meet the quality standard, namely 6 – 9. As for the TSS parameter, it complies with the quality standard, which is 10.58 mg/L below 200 mg/L. The BOD 5 test results meet the quality standard, which is 39.4 mg/L below the quality standard value of 150 mg/L. The results of the COD test of 115 mg/L have met the requirements for the quality standard value of 300 mg/L.